Metataxomics reveals Blastocystis subtypes mixed infections in Colombian children (2023)
ABSTRACT: Blastocystis sp., is an intestinal protist with a broad host range and a high prevalence in human populations worldwide, even in developed Western countries. The publication of conflicting evidence has divided the scientific community about the pathogenic role of this parasite. Even though, genetic studies on Blastocystis sp. revealed associations between genotypes and different pathogenic profiles. Conventionally, the detection of this parasite is based on microscopic or PCR methods, which offer meager or null performance in detecting mixed infections. In this work, we applied a metataxonomic NGS approach targeting the V4 region of the eukaryotic SSU-rRNA gene and classical phylogenetic methods. This approach allowed us to detect Blastocystis sp. in stool samples from infected children living in an urban setting in the city of Medellin attending the same daycare center. Phylogenetic analysis identified the subtypes present in the children as ST1, ST2, and ST3. Besides, mixed infections of subtypes ST1 + ST3 were spotted in 16% of the analyzed stool samples.